The effect of symbiosis strategy on opportunity creation: case study of new ventures in China. (2016) - Cai, Li; Chen, Juanyi; Peng, Xiuqing; Chen, Biao
Opportunity creation generates the great potential for business, yet we know relatively little about how firms create entrepreneurial opportunity. This study compares the opportunity creation strategies of two private high-tech firms in China. We apply case-based approach directly to investigate what factors drive firms to choose symbiosis strategy, how Chinese ventures use symbiosis strategy to create opportunity over time, and how resource combination affects this process. Our evidence suggests that choices of symbiosis strategy are a function of internal and external factors. We also uncover that symbiosis strategy is composed of two complementary dimensions: technology-based symbiosis and market-based symbiosis. Finally, resource combination exerts a moderating effect on the relationship between symbiosis strategy and opportunity creation. We propose a model that extends the literature on opportunity and strategy research.